Competências do professor de Português Língua Estrangeira (PLE) em formação : (re)construção e reflexão - Negri, Marcia Fanti (Universidade Federal de São Carlos, 2014)
This research aims to analyze the performance of teachers (in the process of education) of Portuguese as a foreign language, based on a range of theoretical models of competence. Therefore, a brief summary of the term competence was outlined, starting with the concept of communicative competence and their approaches related to foreign language teachers. This research is based upon theories of competence, communicative competence and competence for foreign language teachers. It includes the following authors teachers: Chomsky (1960), Hymes (1972), Savignon (1972), Widdowson (1978), Canale e Swain (1980), Canale (1983), Bachman (1990), Celce-Murcia et al (1995), as well as Perrenoud (1999), Basso (2001) and Almeida Filho (1993 e 1999). In order to collect data, the following instruments/procedures were used in this investigation: an initial questionnaire which aimed to obtain the teachers’ profile; audio recorded lessons; field notes and a final questionnaire. Afterwards, some criteria were established to analyze the data. Some excerpts of the recorded lessons were selected due to the fact that they show evidence of some competences. Based upon Almeida Filho (1993 e 1999) it is considered that the competences of foreign language teachers can be reconstructed through reflection upon their performance. With this work we aim to contribute to the process of reflection in teacher education in the field of foreign languages, as well as, to the literature regarding foreign language teaching and learning process and, more specifically, to the area of Portuguese as a Foreign Language teaching.
Keywords: Ensino-Aprendizagem; Português Língua Estrangeira; Competências; Reflexão; Formação de professor; LINGUISTICA, LETRAS E ARTES::LINGUISTICA